A bibliometric and content analysis of UP School of Library and Information Studies theses on health sciences librarianship - Celajes, Kia C. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Since trends in health sciences librarianship are mostly drawn from the Western countries like the United States, it is important to know the existing developments in health sciences librarianship in a local context. This study examined the content and bibliometric characteristics of the UP School of Library and Information Studies theses relating to health sciences librarianship from academic year 1996-1997 to 2015-2016. Specifically, the study identified the subjects, different research methods and analytical techniques used in analyzing health sciences librarianship studies, the most cited type of reference material, the most cited author, the most cited book, and the most cited journal publication.